Out of Africa Why People Migrate - Giovanni Carbone (Pubblicazioni ISPI, 2017)
The EU is struggling to cope with the so-called "migration crisis" that has emerged over the past few years. Designing the right policies to address immigration requires a deep understanding of its root causes. Why do Africans decide to leave their home countries? While the dream of a better life in Europe is likely part of the explanation, one also needs to examine the prevailing living conditions in the large and heterogeneous sub-Saharan region. This Report investigates the actual role of political, economic, demographic and environmental drivers in current migration flows. It offers a comprehensive picture of major migration motives as well as of key trends. Attention is also devoted to the role of climate change in promoting migration and to intra-continental mobility (two-thirds of sub-Saharan migrant flows start and end within the region). Two country studies on Eritrea and Nigeria are also included to get a closer sense of local developments behind large-scale migration to Europe.